2016
DOI: 10.1002/hed.24276
|View full text |Cite
|
Sign up to set email alerts
|

Association between multidisciplinary team care approach and survival rates in patients with oral cavity squamous cell carcinoma

Abstract: The association of MDTC with improved outcomes may be potentially explained by a better therapeutic alliance between the patient and the tumor board, and/or a greater thoroughness in clinical management. © 2016 Wiley Periodicals, Inc. Head Neck 38: E1544-E1553, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 25 publications
1
47
0
Order By: Relevance
“…The study cohort demonstrated significantly improved 5‐year rates of cervical regional control ( P < 0.05), OS ( P < 0.01), and disease‐specific survival ( P = 0.01) in those presented at MDT compared to the non‐MDT group. Significant association of MDT with improved survival rates across all stages (1–4) was identified . These findings were associated with the extended role of MDT on patient coordination and follow‐up in that the MDT group demonstrated 90% rates of completion of adjuvant RT or CRT, as originally planned, compared to only 71% and 57% of those not presented ( P < 0.001).…”
Section: Literature Reviewmentioning
confidence: 83%
“…The study cohort demonstrated significantly improved 5‐year rates of cervical regional control ( P < 0.05), OS ( P < 0.01), and disease‐specific survival ( P = 0.01) in those presented at MDT compared to the non‐MDT group. Significant association of MDT with improved survival rates across all stages (1–4) was identified . These findings were associated with the extended role of MDT on patient coordination and follow‐up in that the MDT group demonstrated 90% rates of completion of adjuvant RT or CRT, as originally planned, compared to only 71% and 57% of those not presented ( P < 0.001).…”
Section: Literature Reviewmentioning
confidence: 83%
“…Patients were more likely to complete adjuvant treatment in the MTB group. They concluded that the improved survival from the MTB was multifactorial, allowing better identification of high‐risk patients, better selection of the optimal supportive‐care approaches, and the reduction of treatment‐related morbidity …”
Section: Discussionmentioning
confidence: 99%
“…In head and neck cancer, review in an MTB affects and refines treatment plans in up to 30% to 60% of cases . Despite data showing the effects of MTB, there is a paucity of data showing survival benefit of MTB, with limited studies showing a survival impact in head and neck cancer …”
Section: Introductionmentioning
confidence: 99%
“…Positive experience and good practise outcomes were reported by head and neck oncology teams composed of ENT surgeons, plastic surgeons, maxillofacial surgeons, radiotherapists, radiologists, and oncologists. Their multi-disciplinary approach allows for early, continual communication and meticulous operative planning [2,3].Another positive example of multidisciplinary collaboration is represented by breast reconstruction teams, where breast surgeons, plastic surgeons and oncologists often work closely to treat breast cancer, restore form and contour with excellent results [4].It has also been proposed that orthopaedic and plastic surgeons work collaboratively [1,5]. Several departments are now organizing multidisciplinary meetings for both trauma and oncology, and developing joint operating lists and teams [5].…”
mentioning
confidence: 99%
“…Positive experience and good practise outcomes were reported by head and neck oncology teams composed of ENT surgeons, plastic surgeons, maxillofacial surgeons, radiotherapists, radiologists, and oncologists. Their multi-disciplinary approach allows for early, continual communication and meticulous operative planning [2,3].…”
mentioning
confidence: 99%